Mechanisms to Overcome the Homogenization of Rural Tourism Products and Improve the Competitiveness of Rural Tourist Destinations: A Case Study from China - Yiqing Su; Youyan Wang; Rui Li (Systems)
The competitiveness of rural tourism destinations holds significant implications not only for local livelihood sustainability and regional development but also for the preservation and continuity of human civilization. However, developing countries face a critical challenge where rural tourism destination competitiveness is being progressively undermined by the pervasive homogenization of tourism products. The existing literature demonstrates limited engagement with mitigation strategies for tourism product homogenization in examinations of rural destination competitiveness. This study conceptualizes tourism product homogenization as a manifestation of the tragedy of tourism commons, proposing that self-governance can foster rural tourism destination competitive advantages through resolving such collective action dilemmas. Employing a combined IAD-SES framework, the investigation analyzes interview data from Yuanjia Village in Shaanxi Province, China. The analysis delineates how self-governance dynamically enhances and sustains rural tourism destination competitiveness through four institutional mechanisms: provision rules, appropriation rules, monitoring protocols, and sanctioning systems. Furthermore, the findings reveal that the competitiveness driven by self-governance demonstrates the capacity to align individual interests with collective societal benefits. This research contributes to tourism scholarship by identifying novel institutional determinants of tourism destination competitiveness and proposing a policy framework for addressing product homogenization challenges throughout the rural tourism area life cycle.